Multiplexed, targeted gene editing in Nicotiana benthamiana for glyco‐engineering and monoclonal antibody production - Li, Jin; Stoddard, Thomas J; Demorest, Zachary L; Lavoie, Pierre‐Olivier; Luo, Song; Clasen, Benjamin M; Cedrone, Frederic; Ray, Erin E; Coffman, Andrew P; Daulhac, Aurelie; Yabandith, Ann; Retterath, Adam J; et al. (Plant biotechnology journal, 2016)
Biopharmaceutical glycoproteins produced in plants carry N‐glycans with plant‐specific residues core α(1,3)‐fucose and β(1,2)‐xylose, which can significantly impact the activity, stability and immunogenicity of biopharmaceuticals. In this study, we have employed sequence‐specific transcription activator‐like effector nucleases (TALENs) to knock out two α(1,3)‐fucosyltransferase (FucT) and the two β(1,2)‐xylosyltransferase (XylT) genes within Nicotiana benthamiana to generate plants with improved capacity to produce glycoproteins devoid of plant‐specific residues. Among plants regenerated from N. benthamiana protoplasts transformed with TALENs targeting either the FucT or XylT genes, 50% (80 of 160) and 73% (94 of 129) had mutations in at least one FucT or XylT allele, respectively. Among plants regenerated from protoplasts transformed with both TALEN pairs, 17% (18 of 105) had mutations in all four gene targets, and 3% (3 of 105) plants had mutations in all eight alleles comprising both gene families; these mutations were transmitted to the next generation. Endogenous proteins expressed in the complete knockout line had N‐glycans that lacked β(1,2)‐xylose and had a significant reduction in core α(1,3)‐fucose levels (40% of wild type). A similar phenotype was observed in the N‐glycans of a recombinant rituximab antibody transiently expressed in the homozygous mutant plants. More importantly, the most desirable glycoform, one lacking both core α(1,3)‐fucose and β(1,2)‐xylose residues, increased in the antibody from 2% when produced in the wild‐type line to 55% in the mutant line. These results demonstrate the power of TALENs for multiplexed gene editing. Furthermore, the mutant N. benthamiana lines provide a valuable platform for producing highly potent biopharmaceutical products.